Hamlet Szekspira a tragedie Seneki (Shakespeare’s ‘Hamlet’ and Seneca’s Tragedies) - Hajduk, Jacek (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2015)
In this paper I am discussing some crucial resamblences between ancient tragedy of Seneca the Younger and Hamlet by William Shakespeare. I want to show how important is to have in mind Seneca’s efforts while trying to understand „philosophy” and structure of Hamlet.